2005
DOI: 10.1103/physrevb.71.014519
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the superconducting critical temperature on the number of layers in a homologous series of high-Tccuprates

Abstract: We study a model of n-layer high-temperature cuprates of homologous series like HgBa 2 Ca n−1 Cu n O 2+2n+␦ to explain the dependence of the critical temperature T c ͑n͒ on the number n of Cu-O planes in the elementary cell. Focusing on the description of the high-temperature superconducting system in terms of the collective phase variables, we have considered a semimicroscopic anisotropic three-dimensional vector XY model of stacked copper-oxide layers with adjustable parameters representing microscopic in-pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Several authors have studied the effects of interlayer coupling to understand these features from theoretical point of view. [17][18][19][20] Another important aspect of the multilayered systems is the coexistence of superconductivity and antiferromagnetism in a certain region of the phase diagram. [21][22][23] Such phenomenon has been studied theoretically also using t-J model.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied the effects of interlayer coupling to understand these features from theoretical point of view. [17][18][19][20] Another important aspect of the multilayered systems is the coexistence of superconductivity and antiferromagnetism in a certain region of the phase diagram. [21][22][23] Such phenomenon has been studied theoretically also using t-J model.…”
Section: Introductionmentioning
confidence: 99%
“…The problem reduces then to the evaluation of a determinant of the A N ⊥ (k) matrix (for technical details, we refer readers to Refs. [8,11]). Finally, we arrive at the expression for the critical temperature…”
Section: Modelmentioning
confidence: 99%
“…However, in order to describe YBCO phase diagram, it is necessary to relate the model parameters to the amount of oxygen doping. Therefore, we are using a phenomenological dependence of in-plane microscopic phase stiffness of CuO 2 plane on charge (hole) concentration, which was successfully used to describe properties of superconducting homologous series [8]. Furthermore, the dependence between charge concentration and oxygen amount in YBCO was determined experimentally by Tallon et al and found out to be roughly linear in the superconducting region (charge concentration changes from δ = 0.05 for y = 0.4 to δ = 0.17 for y = 1) [12].…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26] The interlayer hopping is indispensable for the bulk SC state, even if each CuO 2 plane shows superconductivity. [27][28][29][30][31][32][33] Here, we note two kinds of interlayer hoppings in the multilayered cuprates.…”
Section: Introductionmentioning
confidence: 99%